The role of profitability in mediating the influence of funding decisions, investment decisions and company size on company value - I Nyoman Suardhika; Siti Aisyah Hidayati; Nur Aida Arifah Tara (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to examine the effect of profitability in mediating the influence of funding decisions, investment decisions, and company size on the Company's value in 27 companies in the infrastructure sector listed on the IDX Main Board for the period 2017 to 2022. The results showed that funding decisions had a negative insignificant effect, while investment decisions and company size had a significant negative effect on profitability. Furthermore, funding decisions, investment decisions, and profitability have a significant positive effect, while company size has a positive insignificant effect on company value. In the mediation effect test, it was found that profitability was not able to mediate the influence of funding decisions on company value. However, profitability is stated to be able to mediate the respective influence of investment decisions and company size on company value.